Evaluacion de adaptacion de siete hibridos introducidos de Maiz Amarillo (Zea Mays l.) en suelos del Bajo Mayo, region San Martín - Paredes Yume, Alexander (2009)
This research was conducted in the field of EEA "El Porvenir" in the valley of the Lower Mayo, San Martin province, geographically characterized by having the following coordinates: Longitude West 76 5 ', 6 35' south latitude and 356 msnmm, with the purpose to identify the hybrid with higher yield and wide adaptation with superior in grain yield and quality compared to local variety Marginal 28 - T and determine the B / C) of each hybrid compared to local variety Marginal 28 - T. We evaluated the performance and additional vegetative characteristics, using statistical design Randomized complete block (DBCR) with 4 replications and 8 treatments. The planting distance was 0.80 m between rows and 0.35 m between shots with a plant density of 71 428 plants per hectare. Composting was done using the doses of 200-120-100 kg NPK / ha, 50% of applied nitrogen, together with all the phosphorus and potassium to 10 days after sowing and receiving a total rainfall during the growing season 467.4 mm. From the results obtained according to statistical analysis, we conclude that xistió significant differences between treatments, yields ranged from a 5 016 8 362 kg / ha under the hybrid 688 and DOW 2B Marginal 28 local tropical variety, the largest and lower respectively. According to the agronomic characteristics and economic analysis (B / C), it was determined that hybrids 2B DOW 688 and DOW 8480, are promising good yield potential and economically, with a return greater than 60%.